Anti-rheumatoid arthritis effects of traditional Chinese medicine Fufang Xiaohuoluo pill on collagen-induced arthritis rats and MH7A cells - Yin, Qiong; Huang, Qian; Zhang, Hantao; Zhang, Xiaodi; Fan, Chunlan; Wang, Hongping (Frontiers in Pharmacology, 2024)
Background Fufang Xiaohuoluo pill (FFXHL) is a commonly used prescription in clinical practice for treating rheumatoid arthritis in China, yet its specific mechanism remains unclear. This study aims to elucidate the pharmacological mechanisms of FFXHL using both in vivo and in vitro experiments. Methods The collagen-induced arthritis (CIA) rat model was established to evaluate FFXHL’s therapeutic impact. Parameters that include paw swelling, arthritis scores, and inflammatory markers were examined to assess the anti-inflammatory and analgesic effects of FFXHL. Human fibroblast-like synoviocytes (MH7A cells) is activated by tumour necrosis factor-alpha (TNF-α) were used to explore the anti-inflammatory mechanism on FFXHL. Results Our findings indicate that FFXHL effectively reduced paw swelling, joint pain, arthritis scores, and synovial pannus hyperplasia. It also lowered serum levels of TNF-α, interleukin-1β (IL1β), and interleukin-6 (IL-6). Immunohistochemical analysis revealed decreased expression of nuclear factor-kappa B (NF-κB) p65 in FFXHL-treated CIA rat joints. In vitro experiments demonstrated FFXHL’s ability to decrease protein secretion of IL-1β and IL-6, suppress mRNA expression of matrix metalloproteinases (MMP) −3, −9, and −13, reduce reactive oxygen species (ROS) levels, and inhibit NF-κB p65 translocation in TNF-α stimulated MH7A cells. FFXHL also suppressed protein levels of extracellular signal-regulated kinase (ERK), c-Jun Nterminal kinase (JNK), p38 MAP kinase (p38), protein kinase B (Akt), p65, inhibitor of kappa B kinase α/β (IKKα/β), Toll-like receptor 4 (TLR4), and myeloid differentiation primary response 88 (MyD88) induced by TNF-α in MH7A cells. Conclusion The findings imply that FFXHL exhibits significant anti-inflammatory and antiarthritic effects in both CIA rat models and TNF-α-induced MH7A cells. The potential mechanism involves the inactivation of TLR4/MyD88, mitogen-activated protein kinases (MAPKs), NF-κB, and Akt pathways by FFXHL.